Selection of pasture and forage species adapted to changing environmental conditions in Mediterranean climates - Norton M.R.; Volaire F. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Over the last two decades, many agricultural regions of the Earth with Mediterranean climates have suffered from changing climatic conditions in the form of extended periods of intense drought. These droughts have been associated with an increasing awareness of and concern about climate change and the likely future nature of Mediterranean-type climates. Coping with climate change will be a difficult problem to address because most models for Mediterranean-climate regions predict drier and hotter environments such as for example, in south-western Australia and the western Mediterranean Basin. In south-eastern Australia, while the overall amount of rainfall is predicted to decline, summers are expected to receive more rain and winters become drier. Assuming these predictions are correct, the pastures and rangelands of these regions will experience stresses that without intervention or altered management may cause their wholesale collapse. Not only would this seriously reduce the production of food and fibre from grazing animals it would also lead to a decline in the numerous ecosystem services provided by grasslands such as the services which improve and protect soil structure contributing to the sustainability of cropping through the reduction of nitrate leaching and the maintenance of biodiversity. In Australia, pastures research to adapt to these future climate scenarios has so far primarily focussed on improving plant growth models and assessment of the ability of agricultural soils to sequester more atmospheric carbon. Around the Mediterranean Basin, forage plant research is still mainly focussed on annual crops, cereals and irrigated lucerne. In both regions the focus now needs to shift to the development of more climate resilient perennial plants and agronomic systems able to use these more resilient plants efficiently. Pre-breeding research is needed to identify germplasm resources within the major perennial pasture species with enhanced levels of drought and heat tolerance. This paper describes methods to identify and measure two of the important drought tolerance traits used by perennial herbaceous plants, dehydration tolerance and summer dormancy.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)